Salinity tolerance, Na+ exclusion and allele mining of HKT1; 5 in Oryza sativa and O. glaberrima: many sources, many genes, one mechanism? - Platten, John Damien; Egdane, James A.; Ismail, Abdelbagi M. (Springer, 2013)
Cultivated rice species (Oryza sativa L. and O. glaberrima Steud.) are generally considered among the crop species most sensitive to salt stress. A handful of lines are known to be tolerant, and a small number of these have been used extensively as donors in breeding programs. However, these donors use many of the same genes and physiological mechanisms to confer tolerance. Little information is available on the diversity of mechanisms used by these species to cope with salt stress, and there is a strong need to identify varieties displaying additional physiological and/or genetic mechanisms to confer higher tolerance.Here we present data on 103 accessions from O. sativa and 12 accessions from O. glaberrima, many of which are identified as salt tolerant for the first time, showing moderate to high tolerance of high salinity. The correlation of salinity-induced senescence (as judged by the Standard Evaluation System for Rice, or SES, score) with whole-plant and leaf blade Na+ concentrations was high across nearly all accessions, and was almost identical in both O. sativa and O. glaberrima. The association of leaf Na+ concentrations with cultivar-groups was very weak, but association with the OsHKT1;5 allele was generally strong. Seven major and three minor alleles of OsHKT1;5 were identified, and their comparisons with the leaf Na+ concentration showed that the Aromatic allele conferred the highest exclusion and the Japonica allele the least. A number of exceptions to this association with the Oryza HKT1;5 allele were identified; these probably indicate the existence of additional highly effective exclusion mechanisms. In addition, two landraces were identified, one from Thailand and the other from Senegal, that show high tissue tolerance.Significant variation in salinity tolerance exists within both cultivated Oryza species, and this is the first report of significant tolerance in O. glaberrima. The majority of accessions display a strong quantitative relationship between tolerance and leaf blade Na+ concentration, and thus the major tolerance mechanisms found in these species are those contributing to limiting sodium uptake and accumulation in active leaves. However, there appears to be genetic variation for several mechanisms that affect leaf Na+ concentration, and rare cases of accessions displaying different mechanisms also occur. These mechanisms show great promise for improving salt tolerance in rice over that available from current donors.